Organizing the new industrial economy - Baye, Michael R. 1958- (Elsevier/JAI, 2003)
The growing use of the internet by businesses and consumers is rapidly changing the structure, conduct, and performance of different sectors of the global economy. This ten chapter volume on organizing the 'new economy' documents some of these changes, and examines the ramifications for business strategy and public policy. Chapters in this volume explain how the Internet has altered the conduct of firms competing in 'new economy' markets (such as the online market for air travel information), changed the competitive and technological structure of a host of industries, and has impacted the valuation and performance of businesses (including online-retailers). In addition, contributors to this volume document that online price dispersion is ubiquitous worldwide, quantify the value of reputation in online auction markets, and explain optimal business behavior in 'new economy' settings where network effects, product compatibility, and market dynamics are important. The breadth of topics in this volume, coupled with the expertise and diverse backgrounds of its contributors, make 'Organizing the New Industrial Economy' a unique and valuable addition to the growing literature in the area. This volume is part of Emerald's Advances in Applied Microeconomics series - an annual research volume that disseminates frontier research well in advance of journals and other outlets.